Dukungan Sub Sistem Peradilan Pidana Terhadap Perlindungan Saksi dan Korban (Eksistensi Lembaga Perlindungan Saksi dan Korban) (Lex Jurnalica, 2010)
In article 173 of Criminal Code, the protection of witnesses and victims not be clearly defined. It gives authority to board of judges to present a witness to testify without the presence of the suspect. The reason is to let witness to speak and  testify in a more spacious and there is no fear or worry. However, the witness  must have a freedom to express some information without fearless While witnesses are people who saw or felt occurrence of a crime, directly. In Article 1 paragraph (1) of Law 13/2006,  explains that witness is a person who can demonstrate to investigation, prosecution, and examination before the court what he/she heard by him/herself, he/she saw, and / or his/her own experience. While, in Article 1 paragraph (2) victim is a person whom suffers physically, mentally, and / or economic loss caused by a crime. Protection against both of them are great importance in the criminal justice process, this is in line with the legal principle set forth in the constitution where all citizens are equal position before the law (equality before the law), this in order to give protection and legal certainty and  to ensure a good criminal justice process (due Process of law) is very necessary to the protect them (witnesses and / or victims). It is to create a clean and fair trial that can give justice in society.  Furthermore, in the preamble the Act mentioned above, said that law enforcer in searching for and in clarifying about crimes often have difficulties because they could not present witnesses and / or victims , because of threatening of  certain parties, physically and psychologically.Keywords: Tool of Testimony Evidence, Protection of Witnesses, Victims Protection Institution